A scoping review of case law relating to support and treatment for people with Prader-Willi Syndrome. (September 2021) - Murray, Anna; Kuhn, Isla; Gulati, Gautam; Fistein, Elizabeth
Abstract: Background: Prader-Willi Syndrome (PWS) is a complex multisystem genetic disorder associated with several challenges for people with PWS themselves, and for their families and care givers. Support around access to food is a particular issue due to impaired satiety and, because of this, people with PWS eat excessive amounts of food (hyperphagia). Together with other aspects of the PWS phenotype including, in many cases, a reduced sensitivity to pain, hyperphagia results in life-threatening obesity and life-shortening complications for some people with PWS. Restrictions to liberty and/or access to food raise important legal and ethical considerations in the clinical management of children and adults with PWS. Particularly where disagreements arise and, in the absence of comprehensive guidance for care providers, the courts may be called upon to resolve these difficult issues. Aims: 1) To review case-law from English-speaking common law jurisdictions concerning support arrangements for people with PWS with a view to identifying issues that have required the intervention of the courts. 2) To identify principles on which to base clinical guidelines relating to the issues identified, ensuring that such guidelines are consistent with ethical and human rights imperatives. Methods: Westlaw, Westlaw AU, and Lexis Nexis were searched for case law concerning the treatment or support of a person with PWS. Results: Fifteen cases from jurisdictions in Australia, New Zealand, Canada, the United Kingdom and the United States of America met inclusion criteria. Areas requiring judicial decision making included a) detention in psychiatric hospital; b) support in least restrictive environments c) eligibility for support services; d) guardianship; e) access to special education. Judicial decisions are discussed in the context of the United Nations' Convention on the Rights of Persons with Disabilities.